If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + -8) + -8 = 6(x + -3) + 70 Reorder the terms: 6(-8 + 4x) + -8 = 6(x + -3) + 70 (-8 * 6 + 4x * 6) + -8 = 6(x + -3) + 70 (-48 + 24x) + -8 = 6(x + -3) + 70 Reorder the terms: -48 + -8 + 24x = 6(x + -3) + 70 Combine like terms: -48 + -8 = -56 -56 + 24x = 6(x + -3) + 70 Reorder the terms: -56 + 24x = 6(-3 + x) + 70 -56 + 24x = (-3 * 6 + x * 6) + 70 -56 + 24x = (-18 + 6x) + 70 Reorder the terms: -56 + 24x = -18 + 70 + 6x Combine like terms: -18 + 70 = 52 -56 + 24x = 52 + 6x Solving -56 + 24x = 52 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -56 + 24x + -6x = 52 + 6x + -6x Combine like terms: 24x + -6x = 18x -56 + 18x = 52 + 6x + -6x Combine like terms: 6x + -6x = 0 -56 + 18x = 52 + 0 -56 + 18x = 52 Add '56' to each side of the equation. -56 + 56 + 18x = 52 + 56 Combine like terms: -56 + 56 = 0 0 + 18x = 52 + 56 18x = 52 + 56 Combine like terms: 52 + 56 = 108 18x = 108 Divide each side by '18'. x = 6 Simplifying x = 6
| 2(x+1)-7=3x-15 | | 6x=3(x-2)+33 | | 2(x+2)=5(x-1)-6 | | 7(3n+4)=9(4n+7)+4 | | x+5+x=x+7+x+4+x+11 | | 18x-(8x-6)=46 | | 2x+44-3x=3-4x+5 | | 62(z-59)=z+81 | | -8(-8x-6)=16x-22 | | 2a-20.7=a+1.3 | | 21(4+3x)=336 | | 6x^2=6x-39 | | 6t-12t-2t= | | W+w+5w= | | 12+4(z-3)=-3z+5 | | -16x^2+96x-108=0 | | 21+4+3x=336 | | -16x+96x-108=0 | | 2x+5=-6x-11 | | 4x-28=3x+11 | | -5-(-7)-2-(-13)= | | y=1.2x+2.4 | | 6(x+8)=8+5x | | 128x-y=16 | | 9n^2+24n+12=0 | | M=4rt | | d^2ca=b^4c^3a^2 | | 1x+4=-1-4 | | 6(x+7)=11 | | 21x-7=5(4x-3)-8 | | -4(0.50)+4(0.50)=12 | | AB+BC=c |